EWaS3 2018 2018
DOI: 10.3390/proceedings2110603
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection Impacts to Drinking Water Safety—A Review

Abstract: Drinking water supply safety is of paramount importance for human health. Disinfection is considered as one of the most significant water treatment processes as it inactivates pathogens from drinking water. However, disinfection might have adverse effects in human health, as disinfection by-products, blamed for cancer and reproductive/developmental effects, are formed. Many predictive models and optimization tools are developed in the research. However, an early warning system integrating monitoring, modelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…Disinfection byproducts can cause many different types of cancers (5,13,36), but some types are more likely to be developed due to exposure to DBPs. Previous studies showed that the most common cancers in laboratory animals, due to exposure to DBPs, are renal cancer, intestinal carcinoma, hepatocellular tumors, mesothelioma, and 2…”
Section: Resultsmentioning
confidence: 99%
“…Disinfection byproducts can cause many different types of cancers (5,13,36), but some types are more likely to be developed due to exposure to DBPs. Previous studies showed that the most common cancers in laboratory animals, due to exposure to DBPs, are renal cancer, intestinal carcinoma, hepatocellular tumors, mesothelioma, and 2…”
Section: Resultsmentioning
confidence: 99%
“…However, an early warning system integrating monitoring, modelling, and optimization tools is lacking. The disinfection methods and the models developed so far, which present the basic principles for the development of an early warning system, are considered by Tsitsifli and Kanakoudis [109]. It should be mentioned that the WHO has developed guidelines for drinking-water quality in which filtration and disinfection processes are highly considered [110].…”
Section: Discussionmentioning
confidence: 99%
“…While the overall picture looks promising, a review of 17 APRs in northern Chile found that organizations that operate in small remote localities with less than 500 people presented problems in their water quality [33]. Disinfection processes carry their own risks to water quality [34]; however, to the authors' knowledge, no incidences of these problems have emerged in these organizations.…”
Section: Chilean Context Of the Studymentioning
confidence: 99%